Kreatifitas Guru Dalam Mengajar IPA di Mis Al-Ikhlasiah - Fairuz Afifah Kesogihin; Aufa Aufa; Ilma Husnul Sabila; Syabilah Fauziah Ahmad; Tirti Dara Lesatari (Peneliti.net, 2023)
Natural Sciences is a subject that is often found at every level of education, from elementary school to university. Because science itself studies the natural environment around humans, such as natural phenomena that often occur in everyday life. So it is necessary to provide natural science at the elementary school education level to study the surrounding natural environment from an early age so that students can carry out their daily lives properly and can be protected from natural phenomena that surround them. However, there are several obstacles in carrying out the debriefing of natural science. So the purpose of this research is to research the results of teacher creativity in teaching natural science subjects to elementary school children. Natural science is a basic science that must be taught to children from an early age. However, natural science is very difficult and less attractive to children. The role of the teacher here is very much required to provide direction and guidance to children so that they are willing to take lessons and increase the child's interest in studying natural sciences. So that with these challenges, teachers begin to develop new creativities to deal with these problems. This study uses a qualitative method that examines the research object in depth and is scientific in nature. The object of study in this study is the teacher who teaches at the al-ikhlasiah private madrasah ibtida'iyah. The results of this study are the creativity of al-ikhlasiah MIS teachers in teaching natural science to students.